แหล่งการเรียนรู้สถาบันปรีดี พนมยงค์ : การขับเคลื่อนทางด้านศิลปวัฒนธรรม PRIDI BANOMYONG INSTITUTE LEARNING RESOURCE: THE ARTS AND CULTURAL DYNAMICS MOVEMENT - ภู่ทอง พิศรวัส (วารสารสถาบันวัฒนธรรมและศิลปะ, 2014)
บทคัดย่อ การศึกษาเรื่อง แหล่งการเรียนรู้สถาบันปรีดี พนมยงค์ : การขับเคลื่อนทางด้านศิลปวัฒนธรรม มีวัตถุประสงค์เพื่อ 1)ศึกษาการบริหารจัดการของสถาบันปรีดี พนมยงค์ที่ส่งผลต่อการขับเคลื่อนผลงานทางด้านศิลปวัฒนธรรม อันนำไปสู่แหล่งการเรียนรู้ด้านศิลปวัฒนธรรมในสังคมไทย 2)วิเคราะห์และหาความสัมพันธ์ระหว่างการบริหารจัดการพื้นที่และกิจกรรมที่ส่งเสริมการขับเคลื่อนผลงานทางด้านศิลปวัฒนธรรมของสถาบันปรีดี พนมยงค์กับการเปลี่ยนแปลงทางสังคมและการเมืองในยุคปัจจุบันท่ามกลางกระแสโลกาภิวัตน์ โดยวิธีการวิจัยเชิงคุณภาพ ทั้งการรวบรวมข้อมูลเชิงเอกสารที่เกี่ยวข้องกับนายปรีดี พนมยงค์ และสถาบันปรีดี พนมยงค์ ตั้งแต่ช่วงเวลาหลังการเปลี่ยนแปลงการปกครอง จากระบอบสมบูรณาญาสิทธิราชย์มาเป็นการปกครองในระบอบประชาธิปไตยจนกระทั่งถึงปี พ.ศ.2555 และการสัมภาษณ์แบบเจาะลึกจากคณะกรรมการและผู้มีส่วนเกี่ยวข้อง (Key Information) ซึ่งผลการวิจัย พบว่า 1) สถาบันปรีดี พนมยงค์ เป็นองค์กรเอกชนที่จัดตั้งเป็นอนุสรณ์ให้แด่นายปรีดี พนมยงค์ มีความเป็นเอกเทศในการบริหารจัดการที่ไม่อยู่ในกรอบมีความแตกต่างจากหน่วยงานของรัฐ หรือเอกชนโดยทั่วไป ภายใต้แนวความคิดเพื่อการส่งเสริมความรู้ทางด้านประชาธิปไตยผ่านกิจกรรมทางด้านศิลปวัฒนธรรมในทุกๆ แขนง ด้วยกระบวนการที่แตกต่างกัน ให้กับนักเรียน นิสิต นักศึกษาและบุคคลทั่วไป ตามอุดมการณ์และแนวคิดของปรีดี พนมยงค์เป็นหลัก 2) สถาบันปรีดี พนมยงค์ มีการดำเนินกิจกรรมด้านศิลปวัฒนธรรมที่สอดคล้องกับแนวความคิดเกี่ยวกับแหล่งการเรียนรู้ ด้วยการนำเอาศิลปวัฒนธรรมที่เป็นพื้นฐานของสังคมไทย มาสร้างกิจกรรมทางด้านประชาธิปไตยผ่านกระบวนการทางด้านศิลปวัฒนธรรม ที่มุ่งเน้นที่จะให้ความรู้แก่นิสิต นักศึกษาและประชาชนที่เข้ามาหาความรู้เกี่ยวกับประชาธิปไตยและศิลปวัฒนธรรมสถาบันปรีดี พนมยงค์ อย่างไรก็ดี สถาบันปรีดี พนมยงค์ มีข้อจำกัดด้านการดำเนินกิจกรรมสร้างสรรค์ในลักษณะสัญจรตามเมืองใหญ่ เพื่อที่จะเผยแพร่ผลงานและแนวคิดของนายปรีดี พนมยงค์ทางด้านประชาธิปไตย ให้กับคนในชุมชน หรือท้องถิ่น ถือเป็นมุมมองเชิงโครงสร้างทั้งด้านสังคม การเมือง และการศึกษาในระดับประเทศ อันส่งผลต่อการเรียนรู้ทางด้านประชาธิปไตยผ่านกิจกรรมทางด้านศิลปวัฒนธรรมของไทยที่เป็นรากฐานที่สำคัญต่อการพัฒนาประเทศให้ยั่งยืน คำสำคัญ : แหล่งการเรียนรู้ การขับเคลื่อนศิลปวัฒนธรรม Abstract The research entitled “Pridi Banomyong Institute Learning Resource: The Arts and Cultural Dynamics Movement” was aimed 1) to investigate the administration affecting the arts and cultural dynamics movement the results of which contribute to cultural learning in Thai society and 2) to analyze the relation between space as well as activities to support the arts and cultural dynamics movement of Pridi Banomyong Institute and current social and political transformation in the era of globalization. It was qualitative research. The research data was collected from primary and secondary document of Pridi Banomyong Institute during BE 2538 – 2555 and questionnaire form. The findings revealed as follows; 1. Pridi Banomyong Institute was founded by private sector in commemoration of Pridi Banomyong. This establishment implemented administration autonomously in compliance with democracy concept promotion through all kinds of art and cultural activities relying on a wide range of processes. Pridi Banomyong’s democracy maxim and related knowledge, including the realization of the principal factor that influenced democracy learning was expected to be transmitted to the students and the others in terms of democratic freedom and fraternity. Hence, Pridi Banomyong Institute played an important role in enhancing public understanding towards democracy according to Pridi Banomyong’s thoughts and ideology. 2. The action of Pridi Banomyong Institute adopted the normative idea of learning resources defined as surroundings which made one learn successively based on application of social foundation such as arts and cultures to provide democracy activities, unlikely to the public sector or other agencies of the same kind via unlimited administrative processes. Not only would the students be educated with art and culture information, but they also indirectly learned democratic contents. However, the limitation of Pridi Banomyong Institute included impossibility to provide mobile activities in big cities in order to disseminate Pridi Banomyong’s thoughts and ideology of democracy entirely. It was suggested to assign a particular division to deal with local inaccessibility for democracy conceptualization. This solution was nationally considered as a structural perception of society, politics, and education which was believed to have an effect on sustainable development of the country. Keywords : Learning Resource, The Arts and Cultural Dynamics Movement